Direct Kinetic Simulation of the Interaction of an Expanding Plasma Plume with Ambient Gas - Ronald Chan, W. H.; Vazsonyi, Alexander R.; Boyd, Iain D. (IEEE conference record-abstracts - IEEE International Conference on Plasma Science, 2021)
The interaction of a laser pulse with a material surface induces the formation of a plasma plume that expands away from the surface. This laser ablation procedure is relevant to pulsed laser deposition, laser propulsion, inertial confinement fusion, and laser-induced breakdown spectroscopy. The interaction of the plume with a background gas influences the efficiency of the ablation, deposition, and propulsion processes, and is associated with a myriad of accompanying physical mechanisms. For example, a plume expanding into ambient gas of low pressure around 100 mTorr exhibits splitting and sharpening. 1 A definitive mechanistic explanation for laser-induced plasma plume splitting remains an active area of research. 2 The highly transient process is amenable to direct numerical simulation, which can probe the interactions between individual constituents of the plume-gas mixture in a temporally resolved manner to provide detailed physical insights inaccessible by other means. This requires the adoption of appropriate numerical methods and models. Most studies have employed particle kinetic methods, such as the direct simulation Monte Carlo method, to simulate this process. 3,4 Particle methods are subject to statistical noise, which can prove challenging in a transient flow. Direct kinetic methods, which solve the Boltzmann equation in an Eulerian fashion, are more capable of accurately resolving time-evolving flows. In this work, a direct kinetic solver is used to simulate a two-species mixture as a model problem for the laser-induced plume expansion process. A weakly ionized plume is initially concentrated at one end of the simulation domain and allowed to expand into ambient low-pressure gas of a distinct species. We examine the sensitivity of plume expansion, splitting, and sharpening to the employed computational grid, as well as the background gas pressure and collision models.